Manajemen sarana prasarana di RA Ath Thohiriyah Cililin - Aprlliani, Karisya; Sulistia Rahayu Khoerunnisa; Lulu Zulfa Akyuni; Lulu Mamluatul Adibah (ARKA INSTITUTE, 2022)
RA Ath Thohiriyah Cililin is an early childhood education institution that has good and adequate learning facilities and infrastructure. The learning process in accordance with the predetermined early childhood curriculum, such as the management of existing facilities and infrastructure in early childhood education, must comply with existing regulations. The purpose of this study is to describe the procurement, inventory, use, maintenance, accountability. This study uses interview and observation methods with a qualitative approach. The sample of this research is the infrastructure in RA Ath Thohiriyah Cililin. The results of data analysis show that planning, procurement, inventory, use, maintenance, accountability are carried out by the head of RA and all teachers in RA Ath Thohiriyah Cililin. It can be concluded that the management of facilities and infrastructure at RA Ath Thohiriyah Cililin is good.